What Is Pedagogy? Discovering the Hidden Pedagogical Dimension. Issue 1 (15th March 2023) - Friesen, Norm; Su, Hanno
Abstract: What is pedagogy, exactly? Merriam‐Webster defines it simply as "the art, science, or profession of teaching." In contemporary academic discourse, however, pedagogy is generally left undefined — with its apparent implicit meanings ranging anywhere from a specific "model for teaching" (e.g., behaviorist or progressivist instruction) to a broadly political philosophy of education in general (most famously, a "pedagogy of the oppressed"). In this paper, Norm Friesen and Hanno Su follow the Continental pedagogical tradition in giving pedagogy a general but explicit definition. They do so by looking at how pedagogy arises both in everyday life and in school as unavoidably ethical activity undertaken primarily for the sake of the young person or child. Such activities, the authors maintain, are structured not so much by processes, methods, and outcomes, but by irresolvable oppositions and the tensions between them. They illustrate this inductively through a series of images and examples — moving gradually from ones involving parenting and early childhood to ones from elementary and secondary schooling. In this way, Friesen and Su show that pedagogy is not so much one or more ideologically focused or evidence‐based instructional or psychological approaches to be mastered by a professional or teaching specialist. It is instead an independent but ethically informed practical perspective — one that can (and has) been extended to form a distinctively pedagogical theory and discipline. As such, it is something that is not only a part of our everyday life and culture, but arguably of all human cultures.